1986
DOI: 10.1083/jcb.103.2.393
|View full text |Cite
|
Sign up to set email alerts
|

Type VI collagen in extracellular, 100-nm periodic filaments and fibrils: identification by immunoelectron microscopy.

Abstract: Abstract. Filaments and fibrils that exhibit a 100-nm axial periodicity and occur in the medium and in the deposited extracellular matrix of chicken embryo and human fibroblast cultures have been tentatively identified with type VI collagen on the basis of their similar structural characteristics (Bruns, R. R., 1984, J. Ultrastruct. Res.,. Using indirect immunoelectron microscopy and specific monoclonal and polyclonal antibodies, we now report their positive : identification with collagen VI and their distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
128
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 280 publications
(138 citation statements)
references
References 51 publications
10
128
0
Order By: Relevance
“…4. (Bruns et al 1986;Engvall et al 1986;Ball et al 2001;Reale et al 2001;Baldock et al 2003;Ball et al 2003;Knupp et al 2006) In the TM, type VI immunostaining of both heteromorphic aggregates and interband longitudinal sheets has been observed, supporting the model in Fig. 4.…”
Section: Collagenssupporting
confidence: 80%
See 1 more Smart Citation
“…4. (Bruns et al 1986;Engvall et al 1986;Ball et al 2001;Reale et al 2001;Baldock et al 2003;Ball et al 2003;Knupp et al 2006) In the TM, type VI immunostaining of both heteromorphic aggregates and interband longitudinal sheets has been observed, supporting the model in Fig. 4.…”
Section: Collagenssupporting
confidence: 80%
“…(Reale et al 2001) This may relate to the 100 nm repeat structures in the JCT, although this has not been comprehensively studied in detail. (Hessle and Engvall 1984;Bruns et al 1986;Engvall et al 1986;Knupp et al 2006) The type VI collagen N-terminal repeats bind hyaluronan and heparin, while the C-terminal domains are involved in self-assembly. (Kielty et al 1992b;Specks et al 1992;Ball et al 2001;Ball et al 2003) Decorin and biglycan associate with the N-terminal end of the central collagenous domain, affecting fibril formation.…”
Section: Collagensmentioning
confidence: 99%
“…In accordance with previous studies [4,21], we observed that, in areas of normal skin surrounding the haemangiomas, there was only weak staining for type VI collagen in the subpapillary connective tissue near the epidermaldermal junction and in a thin area around nerves and capillaries. Normally, type VI collagen seems not to be an intrinsic basement membrane component [11].…”
Section: Discussionsupporting
confidence: 93%
“…Normally, type VI collagen seems not to be an intrinsic basement membrane component [11]. Based on immunoelectron microscopic investigations it has been suggested that, in a similar manner to most extracellular matrices, type VI collagen in the skin forms a network of filaments 6-10nm thick independent of collagen type I/III fibrils [4,21]. This network seems to anchor collagen type I/III fibres or the basement membranes of large interstitial structures, such as nerves and blood vessels, into surrounding connective tissue [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation